1999
DOI: 10.1039/a900536f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the preparation method on the properties of zirconia-ceria materials

Abstract: Zirconium-cerium mixed oxides were prepared by two methods: (i) sol-gel hydrolysis of alcoholic solutions of zirconium alkoxides (n-propoxide and n-butoxide) in the presence of aqueous solutions of cerium nitrate (method SG) or (ii) coprecipitation of aqueous solutions of zirconyl and cerium nitrates by ammonia (method NP). Dried or calcined solids were characterized by XRD, DTA, BET and oxygen storage capacity (OSC ) measurements, O 2 adsorption was monitored by infrared spectroscopy. Regardless of the zircon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(88 citation statements)
references
References 12 publications
(2 reference statements)
7
81
0
Order By: Relevance
“…[4] Since the pioneering works of Yao and Yu Yao [2] and of Su et al, [5,6] many studies have been devoted to improving knowledge of the kinetics of OSC [7][8][9] and of the mechanisms implicated in surface and bulk oxygen mobility in ceria and related compounds, [10][11][12][13][14] with a special insight into CeZrO x oxides. [15][16][17][18][19] Oxygen diffusivity in these materials can be measured by 18 O/ 16 O isotopic exchange, [20][21][22] while oxygen species (e.g., superoxides, peroxides) that might be involved in the diffusion process can be investigated by electron spin resonance (ESR) [23][24][25][26][27] or FTIR. [18,[28][29][30][31] ESR studies have shown that the presence of a metal (Pt, Rh) drastically changes the nature of the oxygen species; the metal favoring the formation of O À ions instead of superoxide species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Since the pioneering works of Yao and Yu Yao [2] and of Su et al, [5,6] many studies have been devoted to improving knowledge of the kinetics of OSC [7][8][9] and of the mechanisms implicated in surface and bulk oxygen mobility in ceria and related compounds, [10][11][12][13][14] with a special insight into CeZrO x oxides. [15][16][17][18][19] Oxygen diffusivity in these materials can be measured by 18 O/ 16 O isotopic exchange, [20][21][22] while oxygen species (e.g., superoxides, peroxides) that might be involved in the diffusion process can be investigated by electron spin resonance (ESR) [23][24][25][26][27] or FTIR. [18,[28][29][30][31] ESR studies have shown that the presence of a metal (Pt, Rh) drastically changes the nature of the oxygen species; the metal favoring the formation of O À ions instead of superoxide species.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Oxygen diffusivity in these materials can be measured by 18 O/ 16 O isotopic exchange, [20][21][22] while oxygen species (e.g., superoxides, peroxides) that might be involved in the diffusion process can be investigated by electron spin resonance (ESR) [23][24][25][26][27] or FTIR. [18,[28][29][30][31] ESR studies have shown that the presence of a metal (Pt, Rh) drastically changes the nature of the oxygen species; the metal favoring the formation of O À ions instead of superoxide species. [26] The presence of certain impurities in ceria, such as chloride ions, can also affect the nature and amounts of surface oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the oxygen storage capacity (OSC) is generated by interconversion between Ce 4+ and Ce 3+ under oxidative and reductive conditions [5,6]. The OSC of the CeO 2 -ZrO 2 solid solution depends largely on the method of preparation; many physical properties such as crystallinity, crystallite and particle sizes, and homogeneity change depending upon its preparation methods and, thus, influence the OSC [7], and many methods such as solid-state reaction [8], high-energy milling [9], coprecipitation method [10,11], sol-gel method [12,13], citrate complex method [14], polymerized complex method [15], combustion synthesis [16,17], and hydrothermal method [18,19] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…163,164 Kockmann et al 155 and later Niikura et al 101 , however, showed this not to be the case for Au-induced NWs on Ge(001). Kockmann et al 155 showed that, since STM images are a convolution of the surface and the STM tip's electronic structure, the shape of the latter will lead to a variety of STM images (cf.…”
Section: Au Nanowires On Ge(001) a Experimental Backgroundmentioning
confidence: 99%